Formulasi Konsep Pendidikan Akhlak Pada Mata Pelajaran Akidah Akhlak di Madrasah Ibtidaiyah Palembang Dalam Mewujudkan Siswa Yang Berakhlakul Karimah - Noptario Noptario; Fitria Nurliana Zulfa; Mahmud Arif (Peneliti.net, 2023)
Moral education is very important to be obtained by students. In this fast-paced era, the influx of globalization into the country has had a lot of impact on students, one of which is on student morals. The purpose of this research is to reveal the formulation of the concept of moral education in the subject of moral ethics at Madrasah Ibtidaiyah Palembang. The research method used in this research is a qualitative research method with data collection techniques through interviews conducted with 2 Aqidah Akhlak teachers at Madrasah Ibtidaiyah Palembang. While the data analysis technique is done by using data reduction, data presentation and drawing conclusions. The formulation of the concept of moral education carried out by aqidah moral subject teachers in realizing students who have good morals is carried out in several ways, including giving direct examples to students so that students can imitate the behavior of their teachers, using appropriate learning media so that learning in class is interesting and not boring, rewards and punishment to motivate students, and teachers not only teach but familiarize students with applying akhlakhul kharimah in their daily lives so that students are not only cognitively smart but also affectively superior